Momentum in Imperial Russia - Goetzmann, William N.; Huang, Simon (Journal of Financial Economics, 2018)
Some of the leading theories of momentum have different empirical predictions that depend on market composition and structure. The institutional theory predicts lower momentum profits in markets with less agency. Behavioral theories predict lower profits in markets with more sophisticated investors. In this paper, we use a dataset from a major 19th century equity market to test these predictions. We find no evidence to support the institutional theory due to the lack of delegated management. We exploit a regulatory change in the middle of our sample period to test behavioral theories. We find evidence consistent with overreaction theories of momentum.